Associations between total, free and bioavailable 25-hydroxyvitamin D forms with adiponectin and irisin in maternal-neonatal pairs at birth from Greece - Arabi, Tarek Ziad; Fakhoury, Hana M. A.; Tamim, Hani; Chun, Rene F.; Hewison, Martin; AlAnouti, Fatme; Pilz, Stefan; Annweiler, Cedric; Tzimagiorgis, Georgios; Haitoglou, Costas; Karras, Spyridon N. (Frontiers in Endocrinology, 2024)
Background: Apart from the well-established skeletal effects, vitamin D has been explored as a secretagogue influencing various adipokines, including adiponectin and irisin. Recent evidence suggests that specific forms of 25-Hydroxyvitamin D (25(OHD), such as free and bioavailable 25(OH)D, may provide more accurate measurements of vitamin D status. The relationship between vitamin D status and serum irisin and adiponectin concentrations remains largely unexplored, particularly during pregnancy.Methods: We analyzed data from 67 healthy maternal-neonatal pairs from Northern Greece at birth. Biochemical and hormonal tests were conducted on each maternal-neonatal pair. The vitamin D forms were estimated using validated mathematical models. Subsequently, regression analyses were conducted to determine the association between the vitamin D forms and adipokine levels.Results: Bioavailable maternal 25(OH)D was inversely associated with neonatal irisin concentrations [β=-73.46 (-140.573 to -6.341), p=0.034]. No other associations were observed between maternal vitamin D status and neonatal adipokine concentrations. Conclusion: In conclusion, maternal bioavailable vitamin D concentrations are inversely associated with neonatal serum irisin concentrations, warranting further studies to evaluate the underlying mechanisms for this finding.